Representing future urban and regional scenarios for flood hazard mitigation - Jose I. Barredo; Carlo Lavalle; Valentina Sagris; Guy Engelen (European Regional Science Association (ERSA), 2005)
In this paper we analyse urban and regional growth trends by using dynamic spatial models. The objective of this approach is twofold: on the one hand to monitor sustainable development trends and on the other hand to assess flood risk in urban areas. We propose the use of future urban scenarios in order to forecast the effects of urban and regional planning policies. In the last 20 years the extent of built-up areas in Europe has increased by 20%, exceeding clearly the 6% rate of population growth over the same period. This trend contributes to unsustainable development patterns, and moreover, the exposure to natural hazards is increasing in large regions of Europe. The paper is organised in two parts. In the first part we analyse a study case in Friuli-Venezia Giulia (FVG) Region in northern Italy. We analyse several spatial indicators in the form of maps describing population growth and patterns, and the historical growth of built-up areas. Then we show the results of a dynamic spatial model for simulating land use scenarios. The model is based on a spatial dynamics bottom-up approach, and can be defined as a cellular automata (CA)-based model. Future urban scenarios are produced by taking into account several factors –e.g. land use development, population growth or spatial planning policies–. Urban simulations offer a useful approach to understanding the consequences of current spatial planning policies. Inappropriate regional and urban planning can exacerbate the negative effects of extreme hydrological processes. Good land management and planning practices, including appropriate land use and development control in flood-prone areas, represent suitable non-structural solutions to minimise flood damages. The overall effects of these measures in terms of both sustainable development and flood defence can be quantified with the proposed modelling approach. In the second part of the paper we show some preliminary results of a pilot study case. Two future simulations produced by the model were used for a flood risk assessment in Pordenone (one of the four provinces of FVG). In the last 100 years Pordenone has suffered several floods. The two major events were the heavy floods of 1966 (100-year flood event; >500 mm of rain in 36 hours) and 2002 (up to 580 mm of rain in 36 hours). The disastrous consequences of those heavy floods have shown how vulnerable this area is. The flood risk analysis is based on a hydrological hazard map for the Livenza River catchment area, provided by the regional Water Authority. That map covers most of flood hazard areas of Pordenone province. Early results of this study show that the main driving force of natural disasters damage is not only increasing flood hazard, but increasing vulnerability, mainly due to urbanisation in flood prone areas.
Keywords: 330